Unusual increase of cases of myelitis in a pediatric hospital in Argentina - Pérez, Guadalupe (2017)
Fil: Perez, Guadalupe. Servicio de Control Epidemiológico e Infectología. Hospital de Pediatría "Prof. Dr. Juan P. Garrahan"; Argentina.